Cell-Specific Functions of ADAM17 Regulate the Progression of Thoracic Aortic Aneurysm. Issue 3 (20th July 2018) - Shen, Mengcheng; Hu, Mei; Fedak, Paul W.M.; Oudit, Gavin Y.; Kassiri, Zamaneh
Abstract : Rationale: : ADAM17 (a disintegrin and metalloproteinase-17) is a membrane-bound enzyme that regulates bioavailability of multiple transmembrane proteins by proteolytic processing. ADAM17 has been linked to several pathologies, but its role in thoracic aortic aneurysm (TAA) has not been determined. Objective: : The objective of this study was to explore the cell-specific functions of vascular ADAM17 in the pathogenesis and progression of TAA. Methods and Results: : In aneurysmal thoracic aorta from patients, ADAM17 was increased in tunica media and intima. To determine the function of ADAM17 in the major cells types within these regions, we generated mice lacking ADAM17 in smooth muscle cells (SMC; Adam17 f/f /Sm22 Cre/+ ) or endothelial cells ( Adam17 f/f /Tie2 Cre/+ ). ADAM17 deficiency in either cell type was sufficient to suppress TAA dilation markedly and adverse remodeling in males and females (in vivo) although through different mechanisms. ADAM17 deficiency in SMCs prevented the contractile-to-synthetic phenotypic switching in these cells after TAA induction, preventing perivascular fibrosis, inflammation, and adverse aortic remodeling. Loss of ADAM17 in endothelial cells protected the integrity of the intimal barrier by preserving the adherens junction (vascular endothelial-cadherin) and tight junctions (junctional adhesion molecule-A and claudin). In vitro studies on primary mouse thoracic SMCs and human primary aortic SMCs and endothelial cells (± ADAM17 small interfering RNA) confirmed the cell-specific functions of ADAM17 and demonstrated the cross-species validity of these findings. To determine the impact of ADAM17 inhibition in treating TAA, we used an ADAM17-selective inhibitor (PF-548) before or 3 days after TAA induction. In both cases, ADAM17 inhibition prevented progression of aneurysmal growth. Conclusions: : We have identified distinct cell-specific functions of ADAM17 in TAA progression, promoting pathological remodeling of SMC and impairing integrity of the intimal endothelial cell barrier. The dual impact of ADAM17 deficiency (or inhibition) in protecting 2 major cell types in the aortic wall highlights the unique position of this proteinase as a critical treatment target for TAA. Abstract : Supplemental Digital Content is available in the text.